PERLINDUNGAN HUKUM MELALUI PRANATA SURAT TUMBAGA HOLING DALAM MASYARAKAT BATAK ANGKOLA - Sormin, Ihwan; Khairunnisa, Maulida; Suciana Rambe, Dinda (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research analyses how the state protects the existence of surat tumbaga holing institutions as a costitutional right of the Angkola Batak community. This research is a normative legal research that is normative empirical in nature which is legal research to find legal rules in the principle of surat tumbaga holing in accordance with the principles of the Indonesian legal system. Primary data used are legal materials from the library and laws and regulations related to legal protection, social structure and local wisdom. To support this data, secondary data is added from the behaviour and values that live in the Angkola Batak community as a living legal norm. The theory used as an analysis knife in this research is Eugen Erlich's legal sociology, where Erlich sees positive law on the one hand and the law that lives in society on the other. Erlich sees that positive law will be effective if it is in line with and incorporates the values and laws that live in society. The results show that the tumbaga holing letter also has a role in resolving problems or criminal acts that occur, such as adultery, domestic violence, verbal insults, defamation or slander, as well as other criminal acts such as theft that can disrupt public welfare. In addition, the sanctions given as punishment to perpetrators involve actions such as being expelled from their customary community, paying a fine to the victim, apologising to the victim or their family in the presence of customary elders, as well as being obliged to cover all food costs incurred during the settlement of the crime. This reality is guaranteed by the state through Article 18 B paragraph (2) which ensures that the state protects, respects and recognises customary law communities and their traditional rights if they are still alive, in accordance with the principles of the Unitary State of the Republic of Indonesia and implemented through legislation. While juridically, it is determined that judges and constitutional judges as law enforcers are obliged to always follow the development of legal values and community justice in adjudicating and deciding cases before them as contained in the judicial power law.